Trunk and upper arm postures in paper mill work - Heiden, M.; Zetterberg, C.; Mathiassen, Svend (Elsevier, 2019)
The aim of this study was to assess postures and movements of the trunk and upper arm during paper mill work, and to determine the extent to which they differ depending on method of assessment. For each of 28 paper mill workers, postures and movements were assessed during three full shifts using inclinometer registration and observation from video. Summary metrics for each shift, e.g., 10th, 50th, and 90th posture percentile, were averaged across shifts and across workers. In addition, the standard deviation between workers, and the standard deviation between shifts within worker were computed. The results showed that trunk and arm postures during paper mill work were similar to other occupations involving manual materials handling, but the velocities of arm movements were lower. While postures determined by inclinometry and observation were similar on a group level, substantial differences were found between results obtained by the two methods for individual workers, particularly for extreme postures. Thus, measurements by either method on individuals or small groups should be interpreted with caution.